Tax Amnesty Role in Developing National Public Welfare - Tukina, Tukina (Humaniora, 2017)
This article was a descriptive qualitative research. The discussion conducted with descriptive analysis. Basic analysis of the study used observation, seminar, and literature review from the web, book, and journal. The study focused on the national development, tax amnesty, and repatriation. It finds that the most important thing for the people, especially under the economic development, is the public welfare and prosperity that are achieved by tax conducted by the government. The making of tax policy, repatriation, and tax amnesty need to be preceded by the academic paper earnestly and profoundly as a basic philosophical, social, and cultural that can be accepted by the people of Indonesia.